1979
DOI: 10.2503/jjshs.47.448
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Photosynthesis and Respiration during Berry Development in Relation to the Ripening of Delaware Grapes

Abstract: The relationship between berry growth and changes in respiratory rate and photosynthetic C02-assimilation rate during the development of grape berries and seeds was studied in relation to their ripening. (1) The respiratory rate of berries in terms of dry weight basis became high at an early part of Stage I and thereafter decreased rapidly. When expressed on a single berry basis, the respiratory re ate increased rapidly during Stage I through Stage III, but there was a sudden drop at veraison. (2) The rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Dry weight then declined to 90% of maximum values by 115 days after flowering. Based on an average daily respiration rate of 1.9 mg CO 2 evolution per berry (Niimi and Torikata 1979) this decline in dry weight subsequent to maximum values around 95 days can be attributed to respiratory loss of accumulated carbon.…”
Section: Resultsmentioning
confidence: 99%
“…Dry weight then declined to 90% of maximum values by 115 days after flowering. Based on an average daily respiration rate of 1.9 mg CO 2 evolution per berry (Niimi and Torikata 1979) this decline in dry weight subsequent to maximum values around 95 days can be attributed to respiratory loss of accumulated carbon.…”
Section: Resultsmentioning
confidence: 99%
“…In Stage III, there is a change in color and texture of the berries, a further increase in volume due to ac cu mu la tion of sugar and water, and further increase in ABA con cen tra tion to a maximum at the beginning of the phase before a decrease. Many attempts have been made to describe and explain the mechanisms that control the changes in fruit growth rate, in clud ing hypotheses that developmental changes in the pericarp are linked to changes in seeds or result from competition with vegetative growth (Matsui et al, 1985;Niimi and Torikata, 1979;Novello et al, 1999;Staudt et al, 1986). Several plant hormones may play an important role in the growth and development of grape berries (Brenner et al, 1989;Cawthon and Morris, 1982;Inaba et al, 1976;Niimi et al, 1977;Pandey and Singh, 1989;Tromp, 1989).…”
Section: Methodsmentioning
confidence: 99%
“…In grapevine, inflorescences contain chlorophyll from bud burst to berry ripening (Palliotti and Cartechini , Lebon et al , ). Some variations in the inflorescence photosynthetic activity during flower development has already been reported (Niimi and Torikata , , Lebon et al , Sawicki et al ). It was demonstrated that inflorescences are able to assimilate and distribute carbon during flower development, mainly to vegetative organs (Vaillant‐Gaveau et al ).…”
Section: Introductionmentioning
confidence: 79%